FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMILIH HOTEL SYARIAH - Pasya, Shifa Aulia; Noor, Iswan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The emergence of halal tourism aligned with Sharia principles has been a significant development in the tourism industry. One crucial aspect of this trend is the presence of Sharia-compliant hotels, which are increasingly competitive in the hospitality sector. This research aims to identify key factors influencing consumer choices when selecting Sharia-compliant hotels in Batu. Using a quantitative descriptive approach with Likert scale analysis, a sample of 160 participants was randomly selected from various respondents who had stayed in Sharia-compliant hotels in Batu. The research findings reveal that consumers' personal preferences in choosing Sharia-compliant hotels are primarily determined by location, religiosity, price, product quality, and lifestyle.